2019
DOI: 10.18203/2349-2902.isj20192371
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Desarda repair in incarcerated inguinal hernia repair: experience in university hospital

Abstract: Background: Synthetic mesh based hernia repair is usually avoided in contaminated and dirty inguinal hernia repair to minimize the risk of infection. Desarda’s technique is a tissue based inguinal hernia repair method which avoids the use of prosthetic mesh. So this study was conducted with the aim to observe the outcome of Desarda’s technique in incarcerated inguinal hernia repair as an alternative procedure to mesh repair.Methods: This study was conducted in Emergency surgery department KGMU Lucknow. Total 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…We noted a marked difference in the type of anaesthetic used 39% [17] concluded in their RCT that the efficacy of the Desarda technique in respect of the early clinical outcomes of hernia repair is similar to that of Lichtenstein method. However the operator in this study showed that the Desarda repair takes a significantly shorter operative time [18][19][20]. The authors therefore conclude that the Desarda repair for inguinal hernia gives the same or better results when compared with the Lichtenstein Mesh repair with shorter hospital stay, more rapid recovery and avoidance of specific mesh related complications whilst also reducing the cost of surgery.…”
Section: Discussionmentioning
confidence: 82%
“…We noted a marked difference in the type of anaesthetic used 39% [17] concluded in their RCT that the efficacy of the Desarda technique in respect of the early clinical outcomes of hernia repair is similar to that of Lichtenstein method. However the operator in this study showed that the Desarda repair takes a significantly shorter operative time [18][19][20]. The authors therefore conclude that the Desarda repair for inguinal hernia gives the same or better results when compared with the Lichtenstein Mesh repair with shorter hospital stay, more rapid recovery and avoidance of specific mesh related complications whilst also reducing the cost of surgery.…”
Section: Discussionmentioning
confidence: 82%
“…We believe the Desarda technique is an excellent beginning point for developing an optimum strategy. 16,17 Since Desarda's approach was initially published in 2001, debates over its validity and benefits have raged, with some claiming that it is simply a modification of Andrews' method. 6 In comparison to Lichtenstein's technique, many randomized clinical studies were conducted.…”
Section: Discussionmentioning
confidence: 99%
“…18 While Lichtenstein's procedure was associated with four recurrences in an Indian hospital, Desarda technique was associated with no recurrences during a clinical trial. 17 On the other hand, recurrence was caused by the Desarda Group's newly repaired deep internal ring. The exclusion of patients with weak or thin external oblique aponeurosis probably led to the absence of weakness in the posterior wall of the inguinal canal rebuilt in our investigation.…”
Section: Discussionmentioning
confidence: 99%